Nostalgia and mourning in Anthony Bukoski`s literary world of Polish Americans - Caputa, Sonia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Contemporary America has discovered high, cultural, therapeutic, as well as commercial values in the notions of history, memory and nostalgia . Renewed interest in languages of ethnics, their literature and Old World customs constitutes evidence of a surge in ethnic identity .
Keywords: Bukoski, Anthony (1945- ); nostalgia; Polish Americans; folk religiosity